The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004280000271
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of matrix metalloproteinases 1, 2, 3, and 9, tissue inhibitors of matrix metalloproteinases 1 and 2, and α2-macroglobulin in cases of generalized AA- and AL amyloidosis

Abstract: Matrix metalloproteinases (MMPs) degrade basement membranes and connective tissue and play an essential role in the homeostasis of the extracellular matrix which is disrupted by the deposition of amyloid. This immunohistochemical study investigated the distribution pattern of matrix metalloproteinases (MMP-1, -2, -3, and -9) and their inhibitors [alpha 2-macroglobulin (alpha 2-M), tissue inhibitors of MMPs (TIMP)-1, and TIMP-2] in human AA- and AL amyloid deposits. Specimens of liver, kidney, and spleen from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
0
33
1
1
Order By: Relevance
“…27 Thus, AA amyloidosis occurs under conditions that are known to generate significantly increased serum and tissue levels of MMPs, as compared with healthy control individuals, and it is tempting to speculate that these MMPs may influence the pathogenesis of AA amyloidosis. Previously we have shown that MMP-1, -2, and -3 are present within AA deposits, 12 and we hypothesize that MMPs may be involved in the processing of the precursor (SAA) or fibril proteins (AFP). In the present study we believe that we are the first to show that human SAA and AFP are indeed susceptible to proteolytic cleavage by MMPs.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…27 Thus, AA amyloidosis occurs under conditions that are known to generate significantly increased serum and tissue levels of MMPs, as compared with healthy control individuals, and it is tempting to speculate that these MMPs may influence the pathogenesis of AA amyloidosis. Previously we have shown that MMP-1, -2, and -3 are present within AA deposits, 12 and we hypothesize that MMPs may be involved in the processing of the precursor (SAA) or fibril proteins (AFP). In the present study we believe that we are the first to show that human SAA and AFP are indeed susceptible to proteolytic cleavage by MMPs.…”
Section: Discussionmentioning
confidence: 80%
“…However, if redundancy is present for the degradation of SAA and AFP, then why does AA occur or persist? It is possible that the degrading system becomes imbalanced during the course of AA deposition or that the presence of protease inhibitors such as ␣2-macroglobulin, which have been detected in AA deposits, 12 may prevent sufficient degradation. To the best of our knowledge, AFP ending at position 51, 56, 57, or 58 (as generated here by degradation with MMPs) have not been described, which would have indicated in vivo activity of MMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenetic role of metalloendoprotease cleavage in amyloidogenesis has been previously established in another type of systemic amyloidosis, i.e., hereditary gelsolin amyloidosis, in which amyloidogenic low molecular weight fragments of this protein ultimately are specifically released by membrane type 1-MMP (35). Rocken et al were the first investigators to show that MMP-1, MMP-2, and MMP-3 are found in association with AA amyloid deposits but are not observed in light chain amyloidosis (36). Subsequently, in vitro studies confirmed that human SAAs and AA amyloid fibrils are susceptible to proteolytic cleavage by MMPs, generating fragments of different sizes (37).…”
Section: Prevalence Of Aa Amyloidosis In Rheumatic Diseasesmentioning
confidence: 99%
“…These patients have been described previously when histological examination demonstrated the presence of generalized amyloidosis, either AA, AL, or ATTR amyloidosis. 20,21 Age, sex distribution, and underlying diseases are summarized in Table 1. The classification of amyloid was based on immunohistochemistry and clinical history as described elsewhere.…”
Section: Patient Selectionmentioning
confidence: 99%